PERKAWINAN DI BAWAH UMUR DALAM HUKUM ADAT BALI DITINJAU DARI UU NO. 1 TAHUN 1974 TENTANG PERKAWINAN DAN UU NO. 35 TAHUN 2014 TENTANG PERLINDUNGANANAK - Loresta Cahyaning Lintang; Rama Pramu Wicaksono (Universitas Sebelas Maret, 2015)
Purpose of Marriage Act is to create a society that is the rule of law and legal certainty for the people who are bound by marriage with the diversity of culture and the existence of customary law are still inherent in the culture in Indonesia. Where problems in the Marriage Act contained in the validity of underage marriage in Article 7 paragraph (1) and paragraph (2) of the Act 1 of 1974 that